Location of prosthodontic treatment and oral health-related quality of life – An exploratory study. Issue 1 (January 2015) - Sukumar, Smitha; John, Mike T.; Schierz, Oliver; Aarabi, Ghazal; Reissmann, Daniel R.
Abstract Purpose Prosthodontic treatment has a positive effect on oral health-related quality of life (OHRQoL); however, there is a paucity of studies assessing the impact of OHRQoL based on where in the mouth ("location") the treatment is performed. This exploratory study investigated the association of the location (anterior, posterior region) of prosthodontic treatment with magnitude and nature of OHRQoL changes. Methods In this non-randomized prospective clinical study, 190 adult patients (17–83 years) were recruited at baseline and 104 were available for the follow-up analyses. Of those, 50 patients received treatment only in the posterior segment and 54 patients in both anterior and posterior regions. Treatment included conventional fixed partial prostheses, removable prostheses or a combination of both. OHRQoL was assessed with the German language version of the 49-item Oral Health Impact Profile (OHIP) at baseline and the questionnaire was repeated 4–6 weeks post-treatment. Magnitude and effect size of changes in summary and sub-scale scores were calculated and data analyzed. Results Patients experienced a substantially impaired OHRQoL (mean OHIP score: 32.3 points) at baseline and an improvement in OHRQoL of 6.8 OHIP points following treatment. This study showed a greater improvement in OHRQoL in patients treated in both regions compared to those treated in the posterior region alone, especially in the function and aesthetic domains. Conclusions This explorative study suggests that OHRQoL improvement is affected by where prosthodontic treatment is performed in the mouth. Greater understanding of qualitative aspects of reconstructive therapies is needed for improved treatment planning and patient consent.